Impact of magnetic field distribution on performance of 18-vane 5.8 GHz magnetron. Issue 7 (2nd May 2016) - Ding, Shuai; Zang, Rui; Zhou, Hong-Cheng; Wang, Bing-Zhong
Abstract: Impact of magnetic field distribution on the performance of an 18-vane 5.8 GHz magnetron is studied in this paper. The magnetic field distribution of the magnetron is calculated for the ideal and the real cases. Different from the ideal case, the real magnetic field is non-uniformly distributed in the interaction space. Based on the calculation results, the impacts of the non-uniform magnetic field distribution on the output power, oscillation time, and efficiency of the magnetron are studied by cavity hot-test simulation. The obtained simulation results are verified by experiment. The study provides reference basis for further improving the performance of the magnetron.